STUDENTS’ READING ANXIETY IN ENGLISH FOREIGN LANGUAGE CLASSROOM - Jullia Aisyah (Journal of English and Education, 2017)
This research was conducted to investigate students’ reading anxiety in an EFL classroom in a junior high school. There were 33 students of a junior high school in Bandung who participated in this research. Utilizing, qualitative descriptive method, this research investigated the levels of students’ anxiety and the causes of students’ anxiety in English reading class. The data were collected using Foreign Language Reading Anxiety Scale (designed by Saito et al., 1999), a set of questionnaire (adopted from Ahmad et al. (2013)) and an interview to clarify the developed questionnaire. The research found that most of the students perceived anxiety in medium level (51,5%). The causes of students’ reading anxiety were based on then text feature including unknown vocabulary, which becomes the first rank of the causes anxiety followed by the unfamiliar topic, and the last is unfamiliar culture.  From personal factor it was found that fear of making error is the first rank followed by worry about reading.